2021
DOI: 10.1002/jia2.25810
|View full text |Cite
|
Sign up to set email alerts
|

HIV care using differentiated service delivery during the COVID‐19 pandemic: a nationwide cohort study in the US Department of Veterans Affairs

Abstract: IntroductionThe Department of Veterans Affairs (VA) is the largest provider of HIV care in the United States. Changes in healthcare delivery became necessary with the COVID‐19 pandemic. We compared HIV healthcare delivery during the first year of the COVID‐19 pandemic to a prior similar calendar period.MethodsWe included 27,674 people with HIV (PWH) enrolled in the Veterans Aging Cohort Study prior to 1 March 2019, with ≥1 healthcare encounter from 1 March 2019 to 29 February 2020 (2019) and/or 1 March 2020 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 24 publications
(34 reference statements)
0
30
0
Order By: Relevance
“…Included studies primarily used convenience sampling and recruited participants from various sources. Several studies used survey responses or other data (e.g., from electronic health records, interviews) from participants who were previously or currently enrolled in clinical trials or other study cohorts or interventions (n = 12) [ 15 26 ] or who were existing HIV clinic patients (n = 7) [ 27 33 ]. Three studies recruited participants using social media [ 34 – 36 ], one study used participants who completed an separate online survey that linked to a COVID-19 survey [ 37 ], and one study recruited participants using mailing lists [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Included studies primarily used convenience sampling and recruited participants from various sources. Several studies used survey responses or other data (e.g., from electronic health records, interviews) from participants who were previously or currently enrolled in clinical trials or other study cohorts or interventions (n = 12) [ 15 26 ] or who were existing HIV clinic patients (n = 7) [ 27 33 ]. Three studies recruited participants using social media [ 34 – 36 ], one study used participants who completed an separate online survey that linked to a COVID-19 survey [ 37 ], and one study recruited participants using mailing lists [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies looked at the impacts of the pandemic within specific communities living with HIV, including those who identified as Black or LatinX [ 16 , 18 ], identified as a member of the LGBTQ community or MSM [ 23 , 34 , 37 ], identified as Black MSM [ 26 , 35 ], were of older age [ 19 , 38 ], were economically disadvantaged [ 22 , 24 , 28 ], or those who reported substance use [ 21 , 25 , 30 ]. Of the other nine studies that reported participant data (e.g., excluding the two studies that used data provided by Ryan White clinics), seven included varying levels of representation across genders, sexual orientations, races, ethnicities, and other demographic factors [ 15 , 17 , 20 , 29 , 31 , 32 , 36 ]. Two did not provide a demographic overview of the study sample [ 27 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This situation causes difficulties in providing health care to patients in this population. So far, there has been no evidence of major disruption in the continuum of HIV care, which may contribute to a change in the services adapting to the new COVID-19 pandemic situation [12].…”
Section: Introductionmentioning
confidence: 99%